A mental health program for infertile couples undergoing oocyte donation: protocol for a mixed methods study - Shohre Ghelich-Khani; Ashraf Kazemi; Malek Fereidooni-Moghadam; Mousa Alavi (BMC, 2020)
Abstract Background The psychological consequences of infertility in couples undergoing oocyte donation differ culturally, racially, religiously, and legally from other infertile couples undergoing assisted reproductive treatments. Therefore, the inclusion of a mental health program in assisted reproductive services is essential for these couples. As such, the aim of this study is to develop a program for improving the mental health of these couples. Methods This study is designed using an exploratory mixed method and the program based on Talbot and Verrinder model. Different steps of this research include determination of a specific topic for planning (needs assessment), initial design of the program, finalization of the program (using the views of experts in this area), implementation of the program, monitoring of the implementation of the program and evaluation of the program. To perform the first step of Talbot's program, the first phase of the study will be conducted. At first, through a qualitative study, the items of the questionnaire are designed and then its psychometric steps will be performed by a cross-sectional study. In the second and third steps, the classic Delphi technique will be used in four-round for initiation and finalization of the program, and the second phase will be completed. The fourth, fifth and sixth steps of the program including implementation, monitoring of the implementation and evaluation of the program in the future will be performed. Discussion Designing an appropriate program based on the documentations of the qualitative study and evidence can improve the mental health and quality of life of the couples undergoing oocyte donation. The program, based on the measurement of needs, will be implemented using a tool designed specifically for the target population and can be useful in the processes of treatment, education, policymaking and legislation as well as research.